Peningkatan Keterampilan Menulis Puisi Melalui Pendekatan Whole Language - Wildan Fauzi Mubarock (FKIP UNIVERSITAS PAKUAN, 2016)
The research is aimed at improving students’ ability to write poems through the approach of whole language. The research is conducted at Indonesian Language and Literature Study Program in 2014. The instruments used to collect the data are pretest and post-test and also non-test instruments which are questionnaire and observational guidance and the researcher himself. The data analysis approaches used are qualitative and quantitative. The analysis of qualitative data was done by comparing the students’ improvement between pre and post cycle based on the students’ writing. The quantitative data is used for supporting the qualitative data. The improvement of students’ ability can be seen from the process of learning. The process includes: students’ experience in reading, writing, speaking, and listening is directed to language activity so that it is able to improve the students’ ability to write poems. The improvement is seen from the average score of pretest which improved in the posttest. The research result shows that there is improvement of students’ ability to write poems. The pretest shows that students who are able to write poems are 46%. After being treated at the first cycle, there is improvement into 61% or adequate. At the second cycle, there was second treatment and the result shows that the improvement is significant which is 81%. The percentage of students’ improvement is 76% between the first and the second cycles. The difference of effectiveness of the first cycle and the second is 39.6%.